Bilateral varicocele leads to ferroptosis, pyroptosis and necroptosis of human spermatozoa and affects semen quality in infertile men - Sun, Tie Cheng; Li, Dong Mei; Yu, Hong; Song, Ling Li; Jia, Yan Jun; Lin, Li; Zhou, Shan Jie (Frontiers in Cell and Developmental Biology, 2023)
Purpose: This study explored the effects of bilateral varicocele on male semen quality in infertile men and the molecular mechanisms involving ferroptosis, pyroptosis and necroptosis signaling pathways. Methods: Totally, 20 healthy males and 26 patients with bilateral varicocele receiving infertility treatment were enrolled. Semen samples were collected. Basic semen parameters, acrosome integrity and membrane integrity, mitochondrial membrane potential (MMP) and apoptosis rate were compared. Levels of reactive oxygen species (ROS), iron, glutathione (GSH), total superoxide dismutase (T-SOD), and, Catalase (CAT), were detected in human seminal plasma. Relative mRNA expression of Ca 2+-independent phospholipases A2 beta (iPLA 2β), P53, Zinc finger E-box binding homeobox 1 (ZEB1) and GSH-dependent peroxidase 4 (GPX4) were evaluated. Relative protein expression was determined for GPX4, receptor interacting serine/threonine kinase 1 (RIPK1) and receptor interacting serine/threonine kinase 3 (RIPK3), as well as pyroptosis markers of Gasdermin E (GSDME) and heat shock protein 90 (HSP 90). Results: The results revealed that the bilateral varicocele group had significantly higher abnormalities (sperm progressive rate and sperm motility) compared to the control group. Meanwhile, compared to control group, GSH, T-SOD, and CAT levels were reduced in the bilateral varicocele group (P < 0.05). However, the level of ROS and iron were significantly increased (P < 0.05). Relative mRNA expression of P53, iPLA 2β, ZEB1 and GPX4 were reduced. In addition, ROS exposure activated ferroptosis-related signal pathways. RIPK1, RIPK3, GSDME and HSP 90 were increased in bilateral varicocele group. ROS exposure affected signaling pathways related to ferroptosis, necrosis and pyroptosis in human spermatozoa. Conclusion: Bilateral varicocele leads to ferroptosis, pyroptosis and necroptosis of human spermatozoa and affects semen quality in infertile men.